KAJIAN ANALISIS WACANA KRITIS TERHADAP ACARA KOMEDI SENTILAN SENTILUN - Laiya, Rebecca Evelyn (Jurnal Dinamika Pendidikan, 2015)
The purpose of this research is to gain an overview and understanding of the ideology contained in the text of the discourse structure dialogue comedy show of Sentilun Sen-tilun. The method used is the method of Critical Discourse Analysis Norman Fairclough models are limited to the description (text analysis). The findings of this critical discourse studies indicated that there is a positive response from the public however it is loaded with scathing criticism that occurred in political situation in Indonesia and may affect people of Indonesia through positive ideology that is the desire to improve the political and legal understanding of Indonesian society. Based on the analysis of critical dis-course, the comedy show of Sentilan Sentilun is expected to bring changes as follows: (1) the way people view on the campaign in Indonesia; (2) the way people view on the election of the leaders in Indonesia; (3) the way people view on how to be a leader; and (4) the way people view on what should be a leader.Keywords : comedy, ideology, critical discourse analysis